Clinical impact of chronic obstructive pulmonary disease (COPD) verified by the COPD Assessment Test (CAT) can be associated with functional capacity? - Maiara Almeida Alda; Flávio Danilo Mungo Pissulin; Silke Anna Theresa Weber; Ricardo Beneti; Marceli Rocha Leite; Francis Lopes Pacagnelli (Acta Scientiarum. Health Sciences, 2018)
The aim of this study was to investigate the impact of the different degrees of severity of ‘CAT’ in the functional capacity evaluated by the 6-minute walk test (6MWT). This is a cross-sectional study, which included spirometrically defined COPD patients, out of exacerbation period and with motor and cognitive skills necessary to perform the spirometry and the 6MWT and reply to the ‘CAT’ questionnaire. We sorted groups according to the clinical impact proposed by ‘CAT’: mild, moderate, severe and very severe. We included 66 COPD patients, with FEV1 (% pred) averages of 53.1 ± 21.9, 51.4 ± 14.1, 50.6 ± 12.8 and 46.4 ± 13.0, which corresponded to the clinical impact of ‘CAT’, respectively (p > 0.05). The highest ‘CAT’ score, observed on mild, moderate and severe clinical impact did not determine the shortest walking distance in the 6MWT (p < 0.05). However, ‘CAT’ score > 30 (very severe clinical impact) was associated with shorter walking distance in the 6MWT (p < 0.05). We found no negative correlation between ‘CAT’ and 6MWT (p = 0.0707 and r = -0.2479). ‘CAT’ was not associated to 6MWT.